DETECTION OF YERSINIA RUCKERI BY POLYMERASE CHAIN REACTION (PCR) IN INFECTED RAINBOW TROUT (ONCORHYNCHUS MYKISS WALBAUM 1792) - Seker, E.; Karahan, M.; Sarieyyupoglu, M.; Cetinkaya, B. (Pakistian Agricultural Scientists Forum, 2011)
This study was conducted to induce experimental infection in rainbow trout with Y. ruckeri, the causative agent of ERM disease and progress of the disease was then monitored over the time period. Application of PCR for early and accurate diagnosis of infection was also investigated. Total 100 fish were allocated to four experimental and a control group each containing 20 fish. There were 20 aquaria and five fish were housed in each aquaria. There were 4 replicates for each group. Fish, at an average weight of 75 g, were injected intramuscularly with 0.1 ml dilutions of Y. ruckeri at various doses (4x10(8), 1x10(8), 4x10(4) and 1x10(4) per ml) in the experimental groups. Blood samples were collected from fish that showed typical signs of the disease. DNA's extracted from blood samples were subjected to PCR amplification based upon a pair of Y. ruckeri specific primers. Following agarose gel electrophoresis of the PCR products, positive bands with the molecular size of approximately 589 bp which were considered indicative for identification as Y. ruckeri were observed. In addition, isolation and identification of Y. ruckeri from various internal organs of infected fish were made by conventional culture method. The results suggested that early diagnosis of ERM disease can be made while fish are alive and diseased fish can be isolated and treated accordingly which will help decrease economic losses.
Keywords: Enteric red mouth disease; rainbow trout; polymerase chain reaction